Pulitzer-winning author Tracy Kidder: Looking for the soul of the machine makers. (4th March 2017) - Drollette, Dan
ABSTRACT: The Pulitzer Prize-winning author of one of the first mass-market nonfiction books about computing – a topic to which he recently returned – gives his impressions of the effects of emerging new technologies, and more important, the mindset of those who build them.